Incidencia de los medios de comunicación locales en el desarrollo social y cultural del Sector Once de Octubre del Cantón Buena Fe - Chumo Zambrano, Jenny Gissella (2019)
The purpose of this research project is to determine the incidence of local media in the social and cultural development of the Once de Octubre neighborhood of the city of Buena Fe, in order to opt for truthful solutions. Project research will be developed based on deductive and inductive methods, in addition to applying the most suitable strategies for data collection, which will include surveys and interviews as fieldwork, in addition to a thorough bibliographic inquiry, using books as resources documentaries, and also using the technology and scope of the internet that shows us a vast range of valuable information for the development of our research. It will be taken as an object of study to the local media, as well as to the inhabitants of the Once de Octubre neighborhood, giving as a sample the number of 231 people. Each of the specifications and edges applied in the project correlated with our variables were viable to corroborate our hypothesis. In this way it was possible to finish that the design and elaboration of a workshop of contents significantly improved the processes developing in the media regarding the diffusion of cultural contents, and in this way aroused the interest of the citizens that we the main benefited